Effect of the duration between total body irradiation and stem cell infusion on the outcome of allogeneic transplantation with myeloablative conditioning. Issue 7 (August 2015) - Akahoshi, Yu; Kako, Shinichi; Nakano, Hirofumi; Ugai, Tomotaka; Wada, Hidenori; Yamasaki, Ryoko; Ishihara, Yuko; Kawamura, Koji; Sakamoto, Kana; Sato, Miki; Ashizawa, Masahiro; Terasako-Saito, Kiriko; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Limited data are available on the effect of how cyclophosphamide (CY) and total body irradiation (TBI) are administered. We analyzed the effect of the interval from TBI to hematopoietic stem cell transplantation (HSCT) on the outcome of HSCT. Methods Adult patients who underwent HSCT using myeloablative conditioning consisting of TBI and CY were retrospectively analyzed. They were divided into three groups according to the duration between the start of TBI and HSCT (Group A: 2–4 days, Group B: 5–8 days, Group C: 9–10 days). Results Seventy-five adult patients were included. The 3-year overall survival rate was 56, 47, and 77% in Groups A, B, and C, respectively (P = 0.14). Similarly, there was no significant difference among the three groups with respect to progression-free survival (57, 47, and 72%, P = 0.17), relapse rate (32, 37, and 16%, P = 0.29), or non-relapse mortality (8, 14, and 12%, P = 0.81). In addition, we observed no significant difference among the three groups with respect to the incidence of grade II–IV acute graft-versus-host disease (GVHD) (31, 47, and 32%, respectively, P = 0.56) and that of chronic GVHD (23, 23, and 22%, respectively, P = 0.97). Discussion and conclusion Although recipient immune system at HSCT might be affected by the timing of TBI, the duration between the start of TBI and HSCT did not influence the outcome of HSCT using myeloablative conditioning with TBI and CY.